PREPARATION OF SOLID LIPID NANOPARTICLES CONTAINING MANGOSTEEN PERICARP EXTRACT - Diniyanti, Siti Nur (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objectives: The aim of this study was to develop solid lipid nanoparticles (SLNs) containing mangosteen pericarp extract (MPE) to achieve enhanced photoprotection and to provide an alternative to synthetic sunscreens in the market. Materials and Methods: The MPE was prepared using the maceration method, and evaluated for sun protection factor (SPF) value using an ultraviolet (UV)-Vis spectrophotometer. SLNs were prepared through ultrasonication method. Blank-SLNs were formulated using stearic acid (SA) or palmitic acid (PA) as solid lipids at a concentration of 3%. Tween® 80 or polyvinyl alcohol (PVA) was employed as a surfactant with a concentration ranging from 1 to 2%. The obtained blank-SLNs were investigated for their physical characteristics, (i.e., morphology, particle size, polydispersity index [PDI], and zeta potential values). The blank-SLNs with suitable physical characteristics were selected to encapsulate MPE and evaluated for the physical characteristics. Results: The MPE was a brownish viscous substance with an SPF value that ranged from 3.09±0.005 to 27.20±0.05 at a concentration ranging from 0.02 to 0.1 mg/ml. Based on the physical characteristics, the blank-SLNs employing PA or SA with 1% of PVA were selected. The MPE-SLNs were spherical, with a particle size that ranged from 443.51±6.50 to 533.52±16.15 nm; PDI ranged from 0.35±0.008 to 0.459±0.02, and zeta potential value ranged from 18.32±1.37 to −19.03±0.64. The entrapment efficiencies of MPE-PA-SLNs and MPE-SA-SLNs were 83.24±1.37% and 84.17±0.411%, respectively. Conclusion: The results indicated the promising potential of MPE as a UVB photoprotector. The MPE-SLNs were also successfully formulated, but, further study is needed to confirm the potential of MPE-SLNs to be used as a sunscreen, and their stability during storage.